Small and flexible web based framework for teaching QR and AR mobile learning application development - Protopsaltis, Aristidis; Ferguson, J.; Mentzelopoulos, M.; Economou, D. (2015 International Conference on Interactive Mobile Communication Technologies and Learning (IMCL), 2015)
The current paper presents an AR development framework for students to easily make and use small QR linked interactive learning web pages on mobile devices targeted primarily for museums. This framework is extrapolated from an AR UI system using fiducial marker cubes. AR as a platform is just now reaching its full potential. Since smartphones and mobile devices are now at a sufficiently large user base, it is worth looking at the potential for an extremely small form factor delivery system that is flexible, easily modified, and used by educators and students. An easily modifiable AR learning experience will present AR, QR Mobile platform development, interactive museums, and the chosen subject in a new style. This method of flipped learning can be shown to improve not only knowledge of the chosen subject through investigation, but a better understanding of development potentials for the mobile devices now ubiquitous to students.<br
Keywords: flipped; mobile learning; Augmented Reality (AR); User Interface (UI); QR